Early life stress induces visual dysfunction and retinal structural alterations in adult mice - Calanni, Juan Salvador (2023)
Early life stress (ELS) is defined as a period of severe and/or chronic trauma, as well as environmental/social deprivation or neglect in the prenatal/early postnatal stage. Presently, the impact of ELS on the retina in the adult stage is unknown. The long-term consequences of ELS at retinal level were analyzed in an animal model of maternal separation with early weaning (MSEW), which mimics early life maternal neglect. For this purpose, mice were separated from the dams for 2 h at postnatal days (PNDs) 4–6, for 3 h at PNDs 7–9, for 4 h at PNDs 10–12, for 6 h at PNDs 13–16, and weaned at PND17. At the end of each separation period, mothers were subjected to movement restriction for 10 min. Control pups were left undisturbed from PND0, and weaned at PND21. Electroretinograms, visual evoked potentials, vision-guided behavioral tests, retinal anterograde transport, and retinal histopathology were examined at PNDs 60–80. MSEW induced long-lasting functional and histological effects at retinal level, including decreased retinal ganglion cell function and alterations in vision-guided behaviors, likely associated to decreased synaptophysin content, retina-superior colliculus communication deficit, increased microglial phagocytic activity, and retinal ganglion cell loss through a corticoid-dependent mechanism. A treatment with mifepristone, injected every 3 days between PNDs 4 and16, prevented functional and structural alterations induced by MSEW. These results suggest that retinal alterations might be included among the childhood adversity-induced threats to life quality, and that an early intervention with mifepristone avoided ELS-induced retinal disturbances. (Figure presented.).